Understanding Barriers to Environmental Management Accounting Development and Implementation in Waste Management Among South African Municipalities - Nyahuna, Thomas; Doorasamy, Mishelle (Research Centre of Inorganic Materials and Complexs, 2021)
The objective of the study is to explore barriers obstructing the South Africa local government, public sector organization, from developing and implementing environmental management accounting (EMA) to improve municipal waste management from an institutional theory perspective. To attain the purpose of the study, 18 in depth interviews were conducted on 12 Chief Finance Officers and 6 municipal managers from 12 municipalities. Thematic analysis procedures reveals that absence of environmental accounting guidance, lack of employee training and skills, weak environmental legislation and regulations, weak stakeholders’ pressure to apply environmental accounting, and financial barriers are key hindrance of developing EMA in the South African local government.